Cliques just don't make cents - Cook, Julia, 1964- (Building relationships, 2012)
Penny tries to hang with the Coin Clique, but she usually feels left out. Then one day Penny lands in a pocket with the beautiful, gold Sacagawea dollar coin, who starts to teach her how special and valuable she really is. Included in the book are tips for parents, teachers, and counselors on how to help young people, espcially girls, who feel excluded and left out by others.